The Effect of Intrinsic Motivation and Extrinsic Motivation on Women's Entrepreneurship Interest PNPM Mandiri Rural - Sri Winda Hardiyanti Damanik; Limega Candrasa (PT Inovasi Pratama Internasional, 2022)
Study this aim to find out how influence from Intrinsic Motivation and Extrinsic Motivation for Interest in Entrepreneurship in the SPP (Women's Savings and Loans) Group . This research is a research quantitative descriptive. Data used are primary data. Methods of data analysis in research _ this using the s analysis method multiple linear regression to get comprehensive picture about the influence between the variables Intrinsic Motivation and Extrinsic Motivation Against Entrepreneurial Interest with using SPSS 17 for Windows. The results of the hypotheses test show that that : Intrinsic Motivation take effect positive and significant to Entrepreneurial Interest . Meanwhile, this study failed to prove the second hypothesis. In this case, Extrinsic Motivation was found to have no significant effect on Entrepreneurial Interest .